Competition between offline and online retailers with heterogeneous customers - Stefano Colombo; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We consider the spatial competition between two traditional physical (or offline) retailers and an Internet (or online) retailer where the efficiency of the latter differs from that of the former. We assume consumers are heterogeneous across two dimensions: (i) the costs of traveling to either of the offline retailers and (ii) the costs of purchasing from the online retailer. Both dimensions depend on the spatial location of consumers and are independent of each other. We show that the online retailer maximizes its profit at an intermediate level of the consumer disutility of online purchase when its efficiency is low.
Keywords: L13; D43; 330; e-commerce; game theory; horizontal differentiation; vertical differentiation